The Suez Canal: Past Lessons and Future Challenges - Lutmar, Carmela; Rubinovitz, Ziv (Palgrave Studies in Maritime Politics and Security, 2023)
This open access book seeks to provide a survey of historical, geopolitical, economic, and environmental developments in the last 150 years and to highlight future challenges it faces as it pertains to the areas mentioned earlier. It argues that the centrality of the canal-geo-strategically and otherwise-requires a shift in scholarly focus to study the various aspects from an interdisciplinary perspective. This book addresses several gaps in the literature-the first being a lack of a systematic examination of historical aspects in the development of the canal in 150 years. The second is a careful study of the canal's geostrategic importance. The third is a combination of several disciplines that examine the centrality of the Suez Canal.